Pengaruh Perendaman Cairan NaOH dan Volume Serat Terhadap Pengujian Impak Serat Gambas - Irawan, Rizki; Napitupulu, Robert; Sirwansyah Suzen, Zaldy (Manutech : Jurnal Teknologi Manufaktur, 2024)
The use of  fiber composites derived from nature whose properties are no less than synthetic fibers and environmentally friendly has been widely studied. Closely natural gambas plants are  found in Indonesia but are still little studied as composites. The aim of this study is to determine the effect of immersion of 3% and 5% NaOH liquids with fiber volume fractions of 20%, 30% and 40% within 2 hours soaking time on gambas fibers. Thes pecimen made uses  the hand lay-up method combined with the full faktorial method with 2  factors and 3 levels in the first factor and then 2 levels in the second factor which is carried out 3 repetitions, so that 18 data  are obtained.  From the study, the highest test result impact strength value was 0.00493 J / mm2 at a volume fraction of 40% with immersion of 3% NaOH liquid. This means that the influence of the higher the fiber volume fraction, the better the composite impact strength. While the lowest result is found in the voume fraction of 20% with 3% NaOH, which is 0.00173 J / mm2. Based on previous research, the results of this impact test still cannot be used as a substitute for SNI helmet manufacturing materials which have an impact strength value of 0.00972 J / mm2.